Responses of isolated human basilar arteries to 5-hydroxytryptamine, noradrenaline, serum, platelets, and erythrocytes. Issue 7 (July 1975) - Starling, L M; Boullin, D J; Grahame-Smith, D G; Adams, C B; Gye, R S
Abstract : The isolated human basilar artery suspended in Kreb's solution contracts to 5-hydroxy-tryptamine, noradrenaline, and histamine, which stimulate specific receptors. Normal human serum contains an unidentified contractile substance, and erythrocytes relax the artery. Serum and erythrocytes potentiate 5-HT contractions. This preparation is suitable for studying vasoactive substances released during vasospasm after subarachnoid haemorrhage.